Some nutritional properties of cow cheese with goji fruits added - Velciov Ariana-Bianca; Cozma Antoanela; Popescu Georgeta-Sofia; Stoin Daniela; Petcov Andreea Adriana; Megyesi Corina; Rădulescu Laura; Anghel Iasmina-Madalina; Drugă Marioara; Rada Maria; 30th International Symposium on Analytical and Environmental Problems Szeged 2024. október 7-8. (University of Szeged Szeged, 2024)
A number of previous studies have shown that cheese-fruit combinations with synergistic effects could be considered functional foods with potential to promote health. This study aims to obtain and determine some nutritional parameters of cow's milk cheese with goji berries addition, to identify if the combination of cheese – goji fruits can improve the nutritional properties of the cheese. The obtained results showed that the analyzed parameters have the following value limits: 22.58 - 23.65% moisture, 75.32 - 78.65% dry matter, 3.04 - 3.76% minerals (ash), 17.21 - 18.88% fat and 11.91 - 13.25% protein. Compared to plain cheese, the cow cheese with goji added is richer in dry matter (10.95%), minerals (12.60%) and proteins (5.65) and lower amounts of fat (17.13%). In addition, according to some studies, the cheese combined with goji fruits significantly improve the antioxidant, α-glucosidase inhibitory, antimicrobial and immunomodulatory properties of plain cheese. Therefore, cow's cheese with goji added could be an attractive functional food option.
Keywords: Természettudományok; Kémiai tudományok